2012
DOI: 10.2118/154814-pa
|View full text |Cite
|
Sign up to set email alerts
|

The Characteristics of Relative Permeability Curves in Naturally Fractured Carbonate Reservoirs

Abstract: In naturally fractured reservoirs, fractures are the main flowing channels, while matrix is the dominant storage space. The oil/water relative permeability curve for the fracture in this kind of reservoir is very important for water-injection field development. In this study, we conducted experiments on the oil/water relative permeability of carbonate cores from Kenkiyak oil field and compared the differences in relative permeability curves between natural matrix cores and artificial-fractured cores. After the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 14 publications
0
34
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Relative permeability is a basic parameter for characterizing multiphase fluid flow behavior, which has a significant impact on the evaluation of multiphase flow performance. Therefore, many studies have been carried out on the relative permeability in porous media.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Relative permeability is a basic parameter for characterizing multiphase fluid flow behavior, which has a significant impact on the evaluation of multiphase flow performance. Therefore, many studies have been carried out on the relative permeability in porous media.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12] Besides, much effort was devoted to numerical simulations. [13][14][15][16] Burdine studied relative permeability curves by a method which utilized capillary pressure information.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of laboratory experiments, there is little data showing effective stress effects on relative permeability in NFCRs. For this study, the results from experiments conducted by McDonald et al (1991) and Lian et al (2012) indicate that the irreducible wetting phase (water) saturation, S wir , increases with effective confining stress, σ 0 , while the water relative permeability, k rw , shifts to the right. This behavior suggests that the rock becomes increasingly water wet as effective stress increases.…”
Section: Resultsmentioning
confidence: 84%
“…When the permeability of the core is low, the nonlinearity of the concave curve is strong. Lian and Cheng (2012) conducted experiments on the oil-water relative permeability of carbonate cores from the Kenkiyak oil field and compared the differences in relative permeability curves between the natural matrix cores and the artificial fracture cores. Their study showed that water injection should be implemented when reservoir pressure was relatively higher to maintain formation pressure during water flooding and reduce the effect of stress sensitivity.…”
Section: Introductionmentioning
confidence: 99%